Avaliação da eficiência de bionanopartículas na coagulação e seu efeito ecotoxicológico na tratabilidade de efluente da indústria frigorífica - Antunes, Aline dos Santos (2020)
The animal slaughter and meat processing industry is responsible for generating large quantities of effluents containing high loads of contaminants. Usually, in the treatment of this wastewater, inorganic coagulants are used. However, coagulants from natural sources have stood out for presenting advantages in the economic and environmental scope compared to conventional ones. In this context, the present study aimed at evaluating the efficiency of the coagulation/flocculation/sedimentation process using the protein extract of the Moringa seed as a natural coagulant in association with magnetic nanoparticles (bionanoparticles) in the treatment of the raw effluent of a poultry and pork slaughtering and processing industry. Initially, effluent turbidity removal was evaluated when employing saline solutions (KCl and CaCl2) and aqueous solution in the preparation of the Moringa coagulant extrat, and, after that, it was determined the most efficient Moringa dosage in the removal of the same parameter. After the preliminary studies, magnetic nanoparticles and bionanoparticles (BioNPs) were synthesized, and the best conditions for the treatment were defined (mass of nanoparticles used in the BioNPs preparation, coagulant dosage and sedimentation time) evaluating the turbidity and UV254nm removal. Samples of the raw effluent and the treated one were employed in the microbial load and phytotoxicity with the Lactuca sativa bioindicator. Also, the efficiency of the process was evaluated after the reuse of the nanoparticles. In the preliminary study it was identified that the 0.1 M CaCl2 solution and the 750 mg L-1 dosage of Moringa were the most efficient in removing turbidity (91.38%). For the BioNPs use, the best conditions were determined being 60 mg of nanoparticles, 500 mg L-1 of BioNPs and 10 minutes of sedimentation under the influence of an external magnetic field (96.14% turbidity removals and 43.63% UV254nm removals). The use of BioNPs enabled the reduction of the sedimentation time from 2.33 h to 10 min in comparison to Moringa. After the treatment, it was observed high removals of the microbial load of the effluent. In addition, the treated effluent did not inhibit the growth of the Lactuca sativa plant. The reuse of the nanoparticles proved to be efficient, since, after three regeneration cycles, there was a low variation in the removal of turbidity and UV254nm. It is concluded that the BioNPs are efficient for the primary treatment of the slaughterhouse effluent, and additionally, they present advantages such as the reduction of the microbial load, reuse of the nanoparticles and non-toxicity.